VAAFT (VIDEO ASSISTED ANAL FISTULA TREATMENT); NOVEL TECHNIQUE FOR THE TREATMENT OF ANAL FISTULA - Asim Khan, Muhammad; Ullah, Rafat; Kamran, Haider; Zarin, Mohammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: VAAFT (Video Assisted Anal Fistula Treatment) is a novel minimally invasive technique for treatment of Fistula in Ano, which claims superior results compared to current treatment modalities due to the added advantage of real time visualization of the fistula tract and internal opening of the fistula using a fistuloscope. Methods: This is cross sectional study in which 84 patients were selected using consecutive non probability sampling. They underwent VAAFT and were followed to assess for primary healing and continence at 6 weeks, and recurrence at 1 year. Results: In this study, 97.6% participants were male. Mean operating time was 24 minutes while Mean VAS was 3.7±2.2. Healing was observed in 83.2% whereas recurrence was found in 10% at one year. All of the patients had normal sphincteric function post operatively. Conclusion: The results of our study affirm other studies in terms of cure rates, sphincter preservation and fistula recurrence. Studies with larger sample size and long term follow up are required to establish the superiority of VAAFT over the other currently available treatment options for anal fistula.